Um pouco abaixo da superfície: afectos gravados em um corpo migrante - Maciel, Artur Luiz de Souza (2017)
Um pouco abaixo da superfície: afectos gravados em um corpo migrante is a research in art, where investigate and re-signify the spaces in places, from the marks caused by the embedding of my emigrant body to the city of João Pessoa. These brands manage, in addition to my body, aluminum plates that I record in machinico-circular movement, generating mobile devices that are marked by places of the city and that are transposed to other places. As trademarks that are registered in addition to the documentation, companies that work between February 27, 2015 and June 30, 2016, in Joao Pessoa, present a sum of other places. The living experience, which becomes graphic, articulates two-dimensionality to three-dimensionality: it is from the experience of living in the city and its daily struggles that I try to materialize perceptions, sensations, and transform affect into percepts. In material construction these perceptions I make series of engravings on aluminum plates, prints, drawings, photographs, artist books, process reports and videos, which present the path taken for research.